Shu.Maique Sidrap Dimsum Business Development Strategy - Ruskiah Katang; Nurhapsa Nurhapsa; Andi Siti Halimah (Agribusiness Journal, 2025)
This study aims to formulate development strategies for Dimsum Shu. Maique, a culinary business located in Sidenreng Rappang Regency (Sidrap), analyses internal and external factors and determines strategic priorities using the Quantitative Strategic Planning Matrix (QSPM) method. The approach includes the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices to identify the business's strengths, weaknesses, opportunities, and threats. The analysis results show an IFE score of 2.708 and an EFE score of 3.096, placing the business in Quadrant II of the IE Matrix, which supports a grow and build strategy. Through QSPM analysis, the highest-priority strategy identified is recruiting competent human resources, followed by regular product innovation and strengthening relationships with suppliers. These findings provide a strategic basis for the business owner to design effective, targeted development efforts to enhance competitiveness and ensure business sustainability.